Dekolorisasi Beberapa Macam Limbah Cair Batik menggunakan Limbah Baglog Pleurotus ostreatus dengan Waktu Inkubasi Berbeda - R. Roro Theresia Sorta; Sri Lestari; Ratna Stia Dewi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
Liquid waste of batik is dyes waste that will pollute the environment, lowers the quality of water and are toxic to living things. Spent mushroom of  Pleurotus ostreatus can be used as an alternative method decolorize of batik liquid waste. The research aimed to determine the spent mushroom of P. ostreatus ability as an absorbent of Zn and decolorize agent of batik waste, i.e: napthol, indigosol and mixed waste. This research used experimental methods in Completely Randomized Design (CRD) with 9 treatments and 3 replicates. The results showed that the spent mushroom P. ostreatus was able to decolorizing some liquid waste of batik. Optimum incubation time on the decolorization liquid waste of batik on incubation time of 72 hours.